The epidemiology of stroke amongst women in the Asia––Pacific region. (May 2011) - Woodward, Mark; Tsukinoki-Murakami, Rumi; Murakami, Yoshitaka; Suh, Il; Fang, Xianghua; Ueshima, Hirotsugu; Lam, Tai Hing
National data from the Asia––Pacific region suggest that stroke accounts for over 10% of female deaths. With general aging in the region, and longer life expectancies for women than men, action is required to maintain recent improvements in female death rates from stroke. However, local data on incidence and risk factors for stroke amongst women are scarce. Data from 214, 032 women in the Asia Pacific Cohort Studies Collaboration were thus used to investigate the risk factors for stroke in the region. Raised systolic blood pressure and diabetes were found to be key risk factors for both ischemic (IS) and hemorrhagic (HS) stroke. After adjustment for other risk factors, every extra 10 mmHg systolic blood pressure increased risk of IS by 36% and HS by 69%, whilst diabetes increased risk of IS by 170% and HS by 147%. Smoking was also an important risk factor for IS and HS; risk was reduced by quitting.